Study guides

☆☆

Q: Factorization of x2 plus 12x plus 27?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

x2 - 12x + 36 = (x - 6)2

x2+12x+11=0 (x+11)(x+1)=0 x=-11 or x=-1

-x2 + 2x + 48 = (-x - 6)(x - 8)

(x + 1)(x + 5)

x² + 8x + 15 = (x + 5)(x + 3)

Related questions

x2+12x+28Improved Answer:--x2+12x+28 = (-x+14)(x+2) when factored

-((x + 2)(x - 14))

-((x + 2)(x - 14))

x + 12x + 20 = (x + 10)(x + 2)

3x(x2 + 2x - 4)

-2x3 + 2x2 + 12x =(-2x) (x2 - x - 6) =(-2x) (x+2) (x-3)

x2-12x+36 = (x-6)2

x2+12x+5 = 3 x2+12x+5-3 = 0 x2+12x+2 = 0

(-2x3 - 2x2 + 12x) = -2x (x2 + x - 6) = -2x (x + 3) (x - 2)

-(x - 14)(x + 2)

x2 + 12x + 32 = (x + 8)(x + 4)

x2 + 12x + 32 = (x + 4)(x + 8)

People also asked